Atherogenic LOX-1 signaling is controlled by SPPL2-mediated intramembrane proteolysis - Mentrup, Torben (J Exp Med, 2019)
The lectin-like oxidized LDL receptor 1 (LOX-1) is a key player in the development of atherosclerosis. LOX-1 promotes endothelial activation and dysfunction by mediating uptake of oxidized LDL and inducing pro-atherogenic signaling. However, little is known about modulators of LOX-1–mediated responses. Here, we show that the function of LOX-1 is controlled proteolytically. Ectodomain shedding by the metalloprotease ADAM10 and lysosomal degradation generate membrane-bound N-terminal fragments (NTFs), which we identified as novel substrates of the intramembrane proteases signal peptide peptidase–like 2a and b (SPPL2a/b). SPPL2a/b control cellular LOX-1 NTF levels which, following self-association via their transmembrane domain, can activate MAP kinases in a ligand-independent manner. This leads to an up-regulation of several pro-atherogenic and pro-fibrotic targets including ICAM-1 and the connective tissue growth factor CTGF. Consequently, SPPL2a/b-deficient mice, which accumulate LOX-1 NTFs, develop larger and more advanced atherosclerotic plaques than controls. This identifies intramembrane proteolysis by SPPL2a/b as a novel atheroprotective mechanism via negative regulation of LOX-1 signaling.